Governance and net-import dependency on food and agricultural products in Sub-Saharan Africa: Does any causality exist? - Esther N. Mwangi; Fuzhong Chen; Daniel Njoroge (European Journal of Government and Economics (EJGE), 2021)
Though most countries in Sub-Saharan Africa (SSA) are agricultural-based, the region is a net importer of food and agricultural products and experiences the highest level of food insecurity globally. The government have a joint goal of achieving a favourable balance of trade and food security; hence this study examines the causal relationship between quality of governance and net-import dependency on food and agricultural products for 25 SSA countries during the period 1995-2015. Principal component analysis is employed to develop a governance index based on the six worldwide governance indicators and a multivariate panel vector error correction framework applied to infer causality in the short and long run. The results reveal that a higher governance index is correlated with a lower net-import dependency ratio and the relationship is statistically significant. Evidence of unidirectional causality running from governance to net-import dependency is reported in 14 SSA countries, mainly in the long run. In conclusion, improving governance quality could support reduced food and agricultural net-import dependency through promoting agriculture production, exports and consequently reduced trade deficits in the long run. Hence, governance reforms in the region should be placed at the heart of the agricultural development agenda.Though most countries in Sub-Saharan Africa (SSA) are agricultural-based, the region is a net importer of food and agricultural products and experiences the highest level of food insecurity globally. The government have a joint goal of achieving a favourable balance of trade and food security; hence this study examines the causal relationship between quality of governance and net-import dependency on food and agricultural products for 25 SSA countries during the period 1995-2015. Principal component analysis is employed to develop a governance index based on the six worldwide governance indicators and a multivariate panel vector error correction framework applied to infer causality in the short and long run. The results reveal that a higher governance index is correlated with a lower net-import dependency ratio and the relationship is statistically significant. Evidence of unidirectional causality running from governance to net-import dependency is reported in 14 SSA countries, mainly in the long run. In conclusion, improving governance quality could support reduced food and agricultural net-import dependency through promoting agriculture production, exports and consequently reduced trade deficits in the long run. Hence, governance reforms in the region should be placed at the heart of the agricultural development agenda.
Keywords: C59; H11; Q17; 330; agriculture; causality; governance; net-import dependency; Sub-Saharan